Strategy to Increase Interest in Buying “Pisang Pasir” - Ramadhani, Sri; Lestari, Annio Indah; Faiz, Muhammad; Saragih, M. Darul Aswad (Universitas Islam Negeri Sumatera Utara, 2024)
The use of the internet has become an important necessity, especially for Millennials and Generation Z, which plays a major role in the exchange of data and information, including in marketing. This service focuses on utilizing social media as an effective marketing tool in increasing consumer buying interest in Pisang Pasir products. Using Focus Group Discussion and training methods, in-depth interviews were conducted with social media users and business people to evaluate the impact of social media marketing on purchase intention. Results show that effective marketing strategies on social media, such as engaging content and direct interaction, can increase consumer buying interest and trust in the product. These improvements contribute to increased sales and customer loyalty. In addition, product quality remains a key factor in maintaining consumer trust. In conclusion, building consumer trust through credible marketing strategies on social media is an important factor in increasing purchase decisions, which ultimately supports sustainable sales growth and long-term success in an increasingly competitive market.